Transfer of Cytoplasmic Male Sterility to the Female Parents of Heat- and Drought-Resilient Maize (Zea mays L.) Hybrids - Ayyanagouda Patil; Kushal Gowda; Shivananda T. Lakshman; Prakash H. Kuchanur; Gajanan Saykhedkar; Sudha Krishnan Nair; Kisan B. Jadhav; Sharanabasappa Yeri; Gururaj Sunkad; Jayaprakash M. Nidagundi; Vinayan Madhumal Thayil; Pervez H. Zaidi (Agronomy)
Maize is the second most important staple food crop in the world after wheat. For maize hybrid seed production, a prominent step is detasseling in the female parent, which is laborious, time consuming, and increases the hybrid seed cost by 15 to 20 percent. Hence, to overcome this problem, exploitation of male sterility in maize crops gains special significance. In this direction, the research was conducted to transfer cytoplasmic male sterility (CMS-C) from a CMS donor (VL192114) into the female parents (CAL1514 and ZL153493) of heat- and drought-resilient maize hybrids (RCRMH-2 and RCRMH-3) by a marker-assisted backcross scheme. The present research used Diversity Array Technology (DArTag) and Kompetitive Allele Specific PCR (KASP)-based single-nucleotide polymorphic markers for background selection in backcross populations. Genome recovery percentage ranged from 64.25 to 72.70, 78.94 to 87.69 and 82.28 to 90.77 percent in the BC1F1, BC2F1 and BC3F1 population, respectively, in the CAL1514 population, while it was 63.47 to 73.55, 78.16 to 88.76 and 83.96 to 91.81 percent in the BC1F1, BC2F1 and BC3F1 population, respectively, in the ZL153493 population. When the near-isogenic CMS lines of both populations are compared for agro-morphological traits with their recurrent parents, the agronomic qualities of recurrent parents, as well as the attributes of distinctness, uniformity and stability, are shown. Therefore, male sterility-transferred, female lines of RCRMH-2 and RCRMH-3 maize hybrids can be used directly to produce maize hybrid seed without the need of the detasseling process.